Baseline Cardiac Biomarker Levels as Predictors of Cancer Risk in the MESA Cohort - Xinjiang Cai, MD, PhD; Quinn White, BA; W. Craig Johnson, MS; Spencer L. Hansen, PhD; Zeina A. Dardari, PhD; Michael Blaha, MD; Erin D. Michos, MD, MHS; Joao AC. Lima, MD; Christopher R. deFilippi, MD; Matthew J. Budoff, MD; Karol E. Watson, MD, PhD; Robyn L. McClelland, PhD; et al. (JACC: Advances)
Background: Assessing the association between baseline levels of cardiac biomarkers and future cancer risk is critical to understand the cross talk between cardiovascular disease and cancer. Objectives: The authors aimed to determine the association between baseline levels of high-sensitivity cardiac troponin T (hs-cTnT) and N-terminal pro-B-type natriuretic peptide (NT-proBNP) with cancer risk in the prospective MESA (Multi-Ethnic Study of Atherosclerosis) cohort. Methods: We analyzed data from 6,244 MESA participants free of self-reported cancer and cardiovascular disease at baseline. Incident cancer was identified using International Classification of Diseases-9th Revision codes from hospitalizations. Cox proportional hazards models were employed to evaluate the associations of hs-cTnT and NT-proBNP with cancer risk. Likelihood ratio tests assessed whether these associations differed by race/ethnicity or sex. Results: The median age was 61.0 years, with 52.7% being female. Over a median follow-up period of 17.8 years, there were 820 incident cancer events, with an incidence rate of 91.2 cases per 10,000 person-years. Higher incidence rates for all cancers were generally associated with higher baseline hs-cTnT and NT-proBNP levels, especially in the highest quartiles. For all-cancer endpoints, the HRs of hs-cTnT and NT-proBNP, calculated based on the SDs for continuous covariates after standardization, were statistically significant in fully adjusted models (HR: 1.18; 95% CI: 1.09-1.27; P < 0.001; and HR: 2.41; 95% CI: 1.30-4.49; P = 0.006, respectively). Sex and race/ethnicity did not significantly affect any of these associations. Conclusions: In the MESA cohort, higher baseline levels of hs-cTnT and NT-proBNP predicted an increased risk of incident cancer, with no significant differences by race/ethnicity or sex.